Review of Small Hydropower Development Potential in Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Tanzania has a huge but underexploited SHP potential estimated to be within 300-500 MW of technically and economically feasible capacity .this resource base returns to the country's varied topograph,perennial revers emanating from highland catchments and rapidly growing electricity demand within the rural and per-urban setting.this paper looks in a detailed analysis of the development opportunities for SHP ,including hydrology head resource mapping geospatial least-cost siting,and financial modeling with technology option environmental consideration social considerations relating to pathways to bankability.The main priority zones for the development of SHP are Iringa,Mbeya,Ruvuma ,Kigoma,Morogoro and Kilimanjaro where SHP (<10 MW per plant micro <100 kW and min100 kW -MW) can cost effectively provide reliable low-carbon electricity that promotes inclusive rural electrification.The challenges include big upfront capital cost,inadequate technical capacity,environmental risk like siltation and bottlenecks on the regulatory front.it further discusses strategies guiding by the recent studies for tackling such barriers with simplified permitting, concessional financing for early-stage development,capacity building /community participation,better policy incentives and watershed management integration. it is included that the sustainable development of SHPs can greatly enhance the resilience of Tanzania's power system.